Genelleştirilmiş doğrusal modeller ile sigorta şirketlerinde hasar rezervinin tahmini - Arslan, Yusuf (My University, 2018)
Hayat-dışı sigortalarda, hasar talepleri ile hasar dosyasının kapanması arasındazaman farkı mevcuttur. Ayrıca, yasal düzenlemeler, hasarın gecikmeli raporlanması yada yapılan itirazlar, hasar talebinde bulunmanın zaman alması veya kapalı dosyalarınyeniden açılmasına neden olabilmektedir.Sigorta şirketlerinin yükümlülüklerini yerine getirebilmesi için ayrılacak olanhasar rezervlerini doğrun tespit etmesi, şirketin mali yapısının korunması açısındanoldukça önemlidir. Rezerv hesabında kullanılan geçmiş veriler genellikle üçgen merdivenmetodu ile gösterilmektedir. Bu veriler iki zaman ekseninde birbirinden ayrılır. Yatayeksen hasar gelişim yılını ve dikey eksen hasar oluşum yılını göstermektedir.Genelleştirilmiş Doğrusal Modeller hasar rezervlerinin tahmininde etkin bir yoldur.Bu çalışmada, hayat-dışı sigorta şirketinin 2007-2016 yılları arasında trafiksigortası ödenen hasar verileri kullanılmıştır. Gelişim üçgenlerindeki verilerin dağılımınıbelirlemek amacıyla üstel dağılım ailesinden gelen olasılık dağılımları kullanılmıştır.Hasar rezervlerini hesaplanmasında tahmine dayalı tüm dağılımların kullanılmasısağlanmıştır. Karlılık için, Pearson artıklarının yeniden örneklendiği bootstrap yöntemibenimsenmiştir. Tahminleyici dağılımlara sahip olmak için, pratikte en çok kullanılanrisk ölçümleri ve hesaplamada dikkate alınmıştır. Önerilen modelleri analizetmek ve performanslarını karşılaştırmak için gerçek hayattaki veriler üzerindenuygulama yapılmıştır. Uygulama sonuçları tablo ve şekiller ile özetlenmiştir.

In non-life insurance, there is a time-lag between the occurrence of the claim andthe closure of the claim file. In addition to this time-lag, a delay in claims applicationprocess or re-opening of the related file may arise due to certain legal regulations, delayedclaim reporting or objections arisen during the process.Determination of reserves accurately and sufficiently in order to meet theliabilities plays an important role in protecting the financial status for an insurancecompany. Historical data used to calculate reserves are generally presented throughclaims development triangles. These data diverge on two time axes. The horizontal axisindicates the years of development of a claim, when the vertical one indicates the year ofthe occurrence of the claim. The Generalized Linear Models may be accepted as one ofthe most efficient ways to estimate claims reserves.In this study, a dataset of paid losses in the Motor Third Party Liability Insurancebetween 2007 and 2016 of the non-life insurance companies are analyzed. Certainrelevant probability distributions from exponential distribution family are used to definethe distributions of data in development triangles. It is possible to state that almost allpredictive distribution methods are used to calculate these claim reserves. The boostrapmethod, in which the Pearson residuals are resampled, is allocated for profitabilityestimations. Besides, and methods, as two of the most commonly preferredin risk measurement are adopted with the purpose of having the predictive distributions.With the intent of analyzing models and comparing the performances, the real-life dataserve as the basis of calculations conducted. The results obtained through all theseanalysis are presented graphically or in the form of tables.
Keywords: Bootstrap method; Bootstrap metodu; Claims; Claims reserves; Econometric models; Ekonometrik modeller; Genelleştirilmiş doğrusal modeller; Generalized linear models; Hasar; Hasar rezervleri; Insurance; İstatiksel metodlar; Risk measures; Risk ölçümleri; Sigorta ve sigortacılık; Statistical methods; Turkey; Türkiye